Registration of 'CP 14‐1377' sugarcane for organic soils in Florida. Issue 1 (5th January 2023) - Sood, Sushma; Momotaz, Aliya; Baltazar, Miguel; Coto Arbelo, Orlando; Davidson, R. Wayne; Islam, Md. S.; Sandhu, Hardev S.; Zhao, Duli; Gordon, Vanessa S.
Abstract: 'CP 14‐1377' (Reg. no. CV‐211, PI 700115), a new sugarcane (a complex hybrid of Saccharum spp.) cultivar, was developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugar Cane League, Inc. CP 14‐1377 was selected from the polycross (X12‐1500) between CP 03‐1094 and Poly12‐29 (several males) made at Canal Point, FL on 20 Dec. 2012. It was released for cultivation on organic soils in June 2021 because of its higher stalk population, sugar yield, and economic index (profitability) than the reference check, 'CP 96‐1252'. The cane fiber content of CP 14‐1377 (137.00 kg Mg −1 ) was 3% higher than that of CP 96‐1252 and 2% lower than that of 'CP 00‐1101' and 'CPCL 05‐1201'. At the time of its release, CP 14‐1377 was resistant to brown rust [caused by Puccinia melanocephala (H. & P. Sydow)], orange rust [caused by Puccinia kuehnii (E.J. Butler)], smut [caused by Sporisorium scitamineum (Syd., M. Piepenbr., M. Stoll & Oberw)], mosaic (caused by Sugarcane mosaic virus strain E), and ratoon stunt disease [caused by Leifsonia xyli subsp. xyli (Evtsuhenko et al.)]. It was also moderately resistant to leaf scald [caused by Xanthomonas albilineans (Ashby, Dowson)] and Sugarcane yellow leaf virus . It had an acceptable level of freeze tolerance for Florida. CP 14‐1377 had yield and disease traits superior to the widely grown cultivar CP 96‐1252; therefore, CP 14‐1377 has the potential to positively affect sugarcane production in Florida.